Genome comparisons indicate recent transfer of wRi‐like Wolbachia between sister species Drosophila suzukii and D. subpulchrella. Issue 22 (8th October 2017) - Conner, William R.; Blaxter, Mark L.; Anfora, Gianfranco; Ometto, Lino; Rota‐Stabelli, Omar; Turelli, Michael
Abstract: Wolbachia endosymbionts may be acquired by horizontal transfer, by introgression through hybridization between closely related species, or by cladogenic retention during speciation. All three modes of acquisition have been demonstrated, but their relative frequency is largely unknown. Drosophila suzukii and its sister species D. subpulchrella harbor Wolbachia, denoted w Suz and w Spc, very closely related to w Ri, identified in California populations of D. simulans . However, these variants differ in their induced phenotypes: w Ri causes significant cytoplasmic incompatibility (CI) in D. simulans, but CI has not been detected in D. suzukii or D. subpulchrella . Our draft genomes of w Suz and w Spc contain full‐length copies of 703 of the 734 single‐copy genes found in w Ri. Over these coding sequences, w Suz and w Spc differ by only 0.004% (i.e., 28 of 704, 883 bp); they are sisters relative to w Ri, from which each differs by 0.014%–0.015%. Using published data from D. melanogaster, Nasonia wasps and Nomada bees to calibrate relative rates of Wolbachia versus host nuclear divergence, we conclude that w Suz and w Spc are too similar—by at least a factor of 100—to be plausible candidates for cladogenic transmission. These three w Ri‐like Wolbachia, which differ in CI phenotype in their native hosts, have different numbers of orthologs of genes postulated to contribute to CI; and the CI loci differ at several nucleotides that may account for the CI difference. We discuss the general problem of distinguishing alternative modes of Wolbachia acquisition, focusing on the difficulties posed by limited knowledge of variation in absolute and relative rates of molecular evolution for host nuclear genomes, mitochondria, and Wolbachia . Abstract : The Wolbachia, denoted w Suz and w Spc, found in the sister host species Drosophila suzukii and D. subpulchrella are very closely related to wRi, the Wolbachia pervasive in D. simulans, another member of the melanogaster species group of Drosophila . We explain and demonstrate a comparative genomics approach for determining how Wolbachia infections are acquired (i.e., distinguishing horizontal, introgressive versus cladogenic acquisition). Applying our comparative method to genomic data from w Suz, w Spc, and their hosts, we argue that w Suz and w Spc are far too similar to have been acquired cladogenically; horizontal transmission between these sister species' hosts is most plausible.